Advanced image processing techniques for detection and quantification of drusen - Mora, André Teixeira Bento Damas (2010)
Dissertation presented to obtain the degree of Doctor of Philosophy in Electrical Engineering, speciality on Perceptional Systems, by the Universidade Nova de Lisboa, Faculty of Sciences and Technology